Sam Kimble, Revised Ordinances of the City of Manhattan and Rules of the Council 49-50 (1887) - (:unkn) unknown (My University, 1887)
§§ 13-14: Any person who shall give, trade, loan or otherwise furnish any pistol, revolver, or toy pistol by which cartridges or caps may be exploded, or any dirk, bowie-knife sling shot or toy known as "rubber sling shot" or other dangerous weapon, to any minor or to any person of notoriously unsound mind, shall be deemed guilty of a misdemeanor, and shall upon conviction before the Police Judge be fined not less than five nor more than one hundred dollars. § 14. Having Possession of the Same. Any minor who shall have in his possession any pistol, revolver, or toy pistol by which cartridges may be exploded or any dirk, bowie knife, brass knuckles, slung shot or toy known as "rubber sling shot" or other dangerous weapons shall be deemed guilty of a misdemeanor and upon conviction shall be fined not less than one nor more than ten dollars.
Keywords: POSSESSION - MINORS; TRANSFER - MINORS